Variability Studies in Indian Mustard on Normal and Saline Soils - Kumar, D (Annals of Arid Zone, 2016)
Study on variability in 30 genotypes of Indian mustard [Brassica juncea Lnern & coss) indicated higher estimates of GCV, PCV, heritability and genetic advance for number of primary branches and siliquae plant-1 on normal soil; and for seedling emergence. number of siliquae on main shoot, number of secondary branches plant-1 and seed yield on saline soil. Number of siliquae plant-1 on normal soil; and seedling emergence and plant height on saline soil had significant positive association with seed yield. Seedling emergence and plant height exhibited maximum direct positive effects on seed yield on saline soil.